Association Between High-Sensitivity Cardiac Troponin and Risk of Stroke in 96 702 Individuals: A Meta-Analysis. Issue 4 (April 2020) - Broersen, Leonie H.A.; Stengl, Helena; Nolte, Christian H.; Westermann, Dirk; Endres, Matthias; Siegerink, Bob; Scheitz, Jan F.
Abstract : Background and Purpose—: Our study aim was to estimate risk of incident stroke based on levels of hs-cTn (high-sensitivity cardiac troponin), a specific biomarker indicating myocardial injury, in the general population, patients with atrial fibrillation, and patients with previous stroke. Methods—: Embase, PubMed, and Web of Science were searched until March 14, 2019 to identify relevant articles. Randomized controlled trials and cohort studies assessing the risk of incident stroke based on hs-cTn were eligible. Pooled adjusted hazard ratios including 95% CI were calculated using a random-effects model due to study heterogeneity per population, coding of hs-cTn (categorical/continuous data), per hs-cTn subunit (T or I), for low risk of bias, and for all-cause and ischemic stroke separately. Results—: We included 17 articles with 96 702 participants. In studies conducted in the general population (n=12; 77 780 participants), the pooled adjusted hazard ratio for incident stroke was 1.25 (CI, 1.10–1.40) for high versus low hs-cTn (as defined by included studies) during an average follow-up of 1 to 20 years (median 10). When categorical data were used, this was increased to 1.58 (CI, 1.26–1.90). The results were robust when accounting for stroke classification (all-cause stroke/ischemic stroke), hs-cTn subunit, risk of bias, and coding of hs-cTn. In patients with atrial fibrillation (4 studies; 18 725 participants), the pooled adjusted hazard ratio for incident stroke was 1.95 (CI, 1.29–2.62) for high versus low hs-cTn. Due to lack of data (one study, 197 participants), no meta-analysis could be performed in patients with previous stroke. Conclusions—: This meta-analysis suggests that hs-cTn can be regarded as a risk marker for incident stroke, with different effect size in different subgroups. More research about the association between hs-cTn and incident stroke in high-risk populations is needed, especially in patients with history of ischemic stroke. Abstract : Supplemental Digital Content is available in the text.